Redresser les torts : l’abolitionnisme et le contrôle de la criminalité - de Haan, Willem (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1992)
In this article 'abolitionism' will be discussed as a social movement, a theoretical perspective, and a political strategy. Strategies for penal reform will be dealt with and the implications of the abolitionist perspective for crime control will be discussed. As a theoretical perspective, abolitionism takes on the twofold task of providing a radical critique of the criminal justice system while showing that there are other, more rational ways of dealing with crime. It will be argued that what is needed is a wide variety o social responses rather than a uniform state reaction to the problem of crime. Therefore, a reconceptualization of the notions of crime and punishment is offered in the form of the concept of redress. In policy terms it is claimed that social policy instead of crime policy is needed in dealing with the social problems and conflicts that are currently singled as the problem of crime.